1980
DOI: 10.1507/endocrj1954.27.451
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone response to thyrotropin-relesing hormone in cancer patients.

Abstract: Plasma GH responses to TRH were investigated in 50 cancer patients.Out of 50 cancer patients, 33 were found to be responders.At 15, 30 and 60 min after TRH injection, the mean values GH for cancer patients was significantly higher than the corresponding value for normal controls and the base-line level following saline injection in cancer patients (p<0.001).Our results suggests that a possible alteration of hypothalamic-pituitary function regulating GH secretion may occur in patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…We have also demonstrated a significant increase in GH after TRH injection in cancer patients (Kamijo et al, 1980(Kamijo et al, , 1983.…”
supporting
confidence: 57%
“…We have also demonstrated a significant increase in GH after TRH injection in cancer patients (Kamijo et al, 1980(Kamijo et al, , 1983.…”
supporting
confidence: 57%
“…Although the exact mechanism involved in the various diseases which have shown paradoxical responses of serum GH to TRH still remains unclarified, it has been demonstrated that the phenomenon gradually disappears after recovery from these disease. Previous work from our laboratory has revealed (Kamijo et al, 1980) that the phenomenon in cancer patients also gradually diminishes after curative resection of tumors and there was no significant correlation between GH responses to TRH and weight loss. Maeda et al (1970 and proposed that altered metabolism of brain monoamines may change the response of GH to TRH in depression and anorexia nervosa.…”
Section: Discussionmentioning
confidence: 80%
“…Recently we have demonstrated a significant rise in GH levels after TRH injection in cancer patients (Kamijo et al, 1980). The present study has been directed toward evidence of sex difference in the GH response to TRH in cancer patients.…”
mentioning
confidence: 87%
“…Abnormal GH secretion has incidentally been found in other diseases such as cancer (Kamijo et al 1980), diabetes mellitus (Vigneri et al 1976) anorexia nervosa (Meada et al 1976) and chronic liver disease (Panerai et al 1977). Only one of our patients showed abnormal glucose tolerance and none of the cases had impaired liver function.…”
Section: Discussionmentioning
confidence: 99%